2012
DOI: 10.1183/09031936.00073111
|View full text |Cite
|
Sign up to set email alerts
|

Altitude illness is related to low hypoxic chemoresponse and low oxygenation during sleep

Abstract: Altitude illness remains a major cause of mortality. Reduced chemosensitivity, irregular breathing leading to central apnoeas/hypopnoeas, and exaggerated pulmonary vasoconstriction may compromise oxygenation. All factors could enhance susceptibility to acute mountain sickness (AMS).We compared 12 AMS-susceptible individuals with recurrent and severe symptoms (AMS+) with 12 ''AMS-nonsusceptible'' subjects (AMS-), assessing sleep-breathing disorders in simulated altitude as well as chemoresponsive and pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 36 publications
6
36
2
Order By: Relevance
“…Fuji about 2.5-fold (Table 2), which is consistent with the findings of previous studies (Bartsch et al, 2004;Luks, 2012). It is plausible that sleeping at higher altitudes causes hypoxemia, and several studies have found that hypoxemia is associated with AMS (Erba et al, 2004;Koehle et al, 2010;Nespoulet et al, 2012;Nussbaumer-Ochsner et al, 2012). Recently, we reported that arterial oxygen saturation gradually decreased when sleeping overnight at a high altitude, ca.…”
Section: Effect Of Sleeping Altitudesupporting
confidence: 90%
“…Fuji about 2.5-fold (Table 2), which is consistent with the findings of previous studies (Bartsch et al, 2004;Luks, 2012). It is plausible that sleeping at higher altitudes causes hypoxemia, and several studies have found that hypoxemia is associated with AMS (Erba et al, 2004;Koehle et al, 2010;Nespoulet et al, 2012;Nussbaumer-Ochsner et al, 2012). Recently, we reported that arterial oxygen saturation gradually decreased when sleeping overnight at a high altitude, ca.…”
Section: Effect Of Sleeping Altitudesupporting
confidence: 90%
“…Recently, in a group of people exposed to experimental hypoxia (FIO 2 = 80% SaO 2 ), the acute hypoxic ventilatory response at 5 min (HVR5min) was greater in individuals not susceptible to AMS compared to susceptible individuals (Nespoulet et al, 2012). These results support the hypothesis of low chemoreceptor sensitivity as a marker of AMS predisposition (Moore et al, 1986), suggesting high chemo sensitivity as a protective factor for AMS.…”
Section: Sleep Qualitysupporting
confidence: 79%
“…Sleep architecture is affected in all trials, with the most noticeable shifts occurring in the combined HBR condition. There appears to be a direct relationship between breathing stability and mean night SpO 2 when otherwise healthy adults are confined to bed, echoing published data that have reported ventilatory drive changes in patients (Schiffman et al, 1983;Chen and Tang, 1989), and lower hypoxic chemoresponsiveness in susceptible individuals at high altitude (Nespoulet et al, 2012). The initial increase in ventilation during exposure to hypoxia (i.e., hypoxic ventilatory response; HVR) is highly variable (Hirshman et al, 1975).…”
Section: Discussionsupporting
confidence: 60%
“…The initial increase in ventilation during exposure to hypoxia (i.e., hypoxic ventilatory response; HVR) is highly variable (Hirshman et al, 1975). Some studies have stratified test populations into "susceptible" and "resistant" phenotypes when characterizing one's predisposition to suffering AMS and highaltitude pulmonary edema (HAPE) (Hohenhaus et al, 1995;Nespoulet et al, 2012). In one investigation, AMS susceptible patients' night SpO 2 concentrations were ∼5% lower than their non-susceptible counterparts, yet these patients experienced significantly fewer AHI events per hour (18 vs. 33 events per hour; p = 0.038) (Nespoulet et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation